PERAN MODERASI NILAI PERUSAHAAN PADA PENGARUH RISIKO KREDIT DAN TINGKAT KECUKUPAN MODAL TERHADAP TINGKAT PROFITABILITAS: Studi Pada Perusahaan Perbankan Yang Terdaftar Di BEI Tahun 2008-2017 (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2021)
This study aims to analyze the effect of Credit Risk, Capital Adequacy Level which is moderated by the value of the company on the Profitability Level in Banking Companies. The analysis technique in this study uses linear regression analysis with moderation variables. Based on the results of the study indicate that credit risk has no significant effect on the level of profitability, the level of capital adequacy has no significant effect on the level of profitability, credit risk and the level of capital adequacy has no significant effect on the level of profitability with company value as a moderating variable. The magnitude of the effect of Credit Risk and Capital Adequacy Level on Profitability is moderated by the Company Value of 57.9%.